Fatty acid composition and antioxidant capacity in linseed grown as forage in Mediterranean environment - Sulas, Leonardo; Re, Giovanni Antonio; Sanna, Federico; Bullitta, Simonetta; Piluzza, Giovanna (Italian Journal of Agronomy, 2019)
This research was aimed at studying the bromatological traits, fatty acid profile, bioactive compounds, and antioxidant capacity in linseed (Linum usitatissimum L.) shoots harvested at six codified morphological stages. Quality traits were significantly related to cumulated growing degree days from seedling emergence to senescence. The crude protein and ash contents exhibited a gradual decrease and were negatively correlated with morphological stages, whereas cell wall components such as neutral, acid detergent fibers and lignin (NDF, ADF, and ADL) and ether extract (EE) showed a positive correlation. Both ABTS [(2,2’-azinobis (3- ethylbenzothiazoline-6-sulphonic acid) diammonium salt] and DPPH (1,1-diphenyl-2-picrylhydrazyl) assays indicated a reduction in antioxidant capacities from stem extension to senescence, from 16 to 7.1, and 19 to 7 mmol TEAC/100g DW, for ABTS and DPPH, respectively. Significant linear correlation among the antioxidant activity, phenolics, NDF, ADF, ADL, and EE were found showed usually. Total phenolic (9.6-26.4 g GAE kg–1) and total flavonoid (5.2-16.7 g CE kg–1) contents were negatively related with morphological stages. The morphological stage was significantly correlated with oil content, although individual fatty acid content did not. Research gives new insights into the evolution of chemical composition of linseed shoot. Remarkable variations in quality traits, fatty acid contents, bioactive compounds, and antioxidant capacity evidence the possibility to use green linseed in animals’ diet, also suggesting the exploitation of linseed plant as forage source.